Impact of Antimicrobial Stewardship Interventions on Antimicrobial Utilization in Asymptomatic Bacteriuria. (August 2021) - Shah, Punit J.; Ike, Chiamaka; Thibeaux, Meghan; Rodriguez, Emilyn; Maddox, Shermel-Edwards; Daoura, Nicolas
Background: Antimicrobial therapy for asymptomatic bacteriuria (ASB) is often unnecessary and is a common reason for inappropriate antimicrobial use in hospitalized patients. Unnecessary ASB treatment leads to collateral damage such as resistance, and Clostridium difficile infections. This study evaluated the impact of interdisciplinary antimicrobial stewardship interventions on antimicrobial utilization in ASB.Methods: This was a quasi-experimental institutional review board (IRB)-approved study evaluating the impact of antimicrobial stewardship on antibiotic utilization for ASB in a pilot medical-surgical unit. The control phase was from August-October 2017 and the postintervention phase was from December-March 2018. In the control phase, electronic medical records of patients with positive urine cultures were retrospectively reviewed. Patients were classified as either having ASB or urinary tract infection (UTI) based on the absence or presence of UTI symptoms documented in the medical record. The intervention phase consisted of educational in-services to providers, nurses, and pharmacists. Clinical pharmacists for the pilot unit utilized an electronic real-time surveillance system to identify patients with positive urine cultures. With nurses' collaboration, clinical pharmacists classified these patients as either having UTI or ASB. Stewardship interventions were made in real-time to discontinue antibiotics in patients with ASB.Results: There were 65 and 77 patients with bacteriuria in the pre- and postintervention phases. Among these, ASB was present in 29 (45%) and 27 (35%) patients, respectively. After excluding those receiving antibiotics for concurrent nonurinary indications, the combination of education with pharmacist and nursing interventions decreased unnecessary ASB treatment from 18 (62%) to 6 (22%) patients (relative risk: 0.36, 95% confidence interval: 0.16-0.72, P = .003).Conclusion: The findings of this study highlight the importance of interdisciplinary interventions in reducing unnecessary antimicrobial therapy for the treatment of ASB. With increasing antimicrobial resistance, healthcare institutions should evaluate the role of these interdisciplinary interventions to reduce unnecessary treatment for ASB.